Mapping the Research Landscape of Formative Assessment in Higher Secondary Schools: A Bibliometric Study - Saeed, Khaulath; et al., (European Journal of Social Science Education and Research, 2026)
Purpose: This study aims to map the research landscape of formative assessment in higher secondary schools by examining publication patterns, key contributors, thematic structures, conceptual linkages, country collaboration networks, and influential institutions. The goal is to provide a comprehensive understanding of how the field has evolved and where major scholarly contributions are concentrated. Design/methodology/approach: A bibliometric research design supported by science-mapping techniques was employed. Data were retrieved from the Scopus database (2000–2024). A total of 484 publications were analyzed after applying PRISMA-inspired screening procedures. Descriptive statistics were generated using Excel, while VOSviewer was used to construct co-authorship, keyword co-occurrence, citation, intellectual structure, and country collaboration networks. Findings: Results show a significant increase in research output after 2020, indicating growing global interest in formative assessment. A small core of authors drives the field, while the United States, Indonesia, the United Kingdom, Hong Kong, and Norway emerge as leading contributors. Keyword analysis identified 143 core concepts forming 12 thematic clusters, with “formative assessment,” “assessment for learning,” “feedback,” and “self-assessment” at the center. Intellectual structure mapping revealed 15 thematic clusters highlighting strong theoretical foundations, methodological diversity, and increasing integration of digital learning environments. Eight distinct country collaboration clusters demonstrate regionally concentrated yet globally connected research patterns. Research limitations/implications: This study is limited to the Scopus database; future research may integrate additional sources for broader coverage. The findings provide insights for policymakers, researchers, and educators seeking to advance formative assessment practices. Originality/value: This is one of the few studies offering a comprehensive, data-driven overview of formative assessment research specifically within higher secondary education, integrating intellectual, conceptual, and geographical perspectives.
Keywords: Quality education, formative assessment; assessment for learning; bibliometric analysis; secondary education; VOSviewer